Rancang Bangun Website Baitul Malwa Tamwil Daarut Tauhid Ciputat - Pratama, Adihitya; Rahman, Raden Aulia (Universitas Trilogi, 2019)
Baitul Malwa Tamwil (BMT) Daarut Tauhid is a bank based on Islamic law in handling financial transactions such as savings, loans and financing. BMT Daarut Tauhid Ciputat in serving information for customers has not been maximized, that is limited to only using SMS broadcast services, the use of brochures, monthly tabloids and flyers. This causes some of the information needed by customers to be conveyed quickly and accurately. Function of website to present information about activities and things needed by customers of BMT Daarut Tauhid Ciputat. The results of this study can be applied by BMT Daarut Tauhid Ciputat in improving the quality of service to customers.